Experimental analysis of mode I crack propagation in adhesively bonded joints by optical backscatter reflectometry and comparison with digital image correlation. (December 2021) - Lima, R.A.A.; Perrone, R.; Carboni, M.; Bernasconi, A.
Highlights: Optical Backscatter Reflectometry was used to monitor DCB adhesive joints. OBR allows for the onset of damage in the bondline to be identified. Indications by OBR are in agreement with Digital Image Correlation; Process zone size could be estimated combining DIC and visual inspection. Abstract: The relationship between the response of backface strain distributed sensing by Optical Backscatter Reflectometry and the damage in the adhesive was studied using double cantilever beam specimens. Digital Image Correlation and visual inspection provided information about the crack-tip position and the extension of the cohesive process zone. The comparison between the features of the backface strain pattern and the position and size of the cohesive zone led to the conclusion that, for the studied adhesive, backface distributed sensing allows for the onset of plastic deformations ahead of the crack-tip to be identified, opening new perspectives for fatigue crack monitoring and in-service measurements.